Peri‐anesthetic hypothermia in rodents: A factor to consider for accurate and reproducible outcomes in orthopedic device‐related infection studies. Issue 3 (12th July 2022) - Constant, Caroline; Moriarty, Thomas F.; Arens, Daniel; Pugliese, Brenna; Zeiter, Stephan
Abstract: Orthopedic device‐related infection (ODRI) preclinical models are widely used in translational research. Most ODRI models require induction of general anesthesia, which frequently results in hypothermia in rodents. This study aimed to evaluate the impact of peri‐anesthetic hypothermia in rodents on outcomes in preclinical ODRI studies. A retrospective analysis of all rodents that underwent surgery under general anesthesia to induce an ODRI model with inoculation of Staphylococcus epidermidis between 2016 and 2020 was conducted. A one‐way multivariate analysis of covariance (one‐way MANCOVA) was used to determine the fixed effect of peri‐anesthetic hypothermia (hypothermic defined as rectal temperature <35°C) on the combined harvested tissue and implant colony‐forming unit (CFU) counts, and having controlled for the study groups including treatments received, duration of surgery and anesthesia, and study period. The results showed a significant effect of peri‐anesthetic hypothermia on the post‐mortem combined CFU counts from the harvested tissue and implant(s) ( p  = 0.01) when comparing normo‐ versus hypothermic rodents. Using Wilks' Λ as a criterion to determine the contribution of independent variables to the model, peri‐anesthetic hypothermia was the most significant, though still a weak predictor, of increased harvested CFU counts. Altogether, the data corroborate the concept that bacterial colonization is affected by abnormal body temperature during general anesthesia at the time of bacterial inoculation in rodents, which needs to be taken into consideration to decrease infection data variability and improve experimental reproducibility.